Pulverous ferrous waste processing by agglomeration. (February 2019) - Lupu, O; Zgripcea, L; Socalici, A; Popa, E; Hărău, C
Abstract: The current paper presents the results obtained after the laboratory testing of the of agglomeration process of pulverous ferous waste. The obtained products are destined for use in the steel industry, as raw material for the production of steel. When choosing the proceedure and technologies of capitalization we took into consideration the features of the waste, the destination of the obtained product and the existing processing facilities. The superior valorification of iron and steel waste represents an important matter because their transformation into by-products leads to a rational use of raw material and energy resources, thus ensuring both the satisfaction of human society and the protection of the environment.